2015
DOI: 10.5194/acp-15-1029-2015
|View full text |Cite
|
Sign up to set email alerts
|

Detailed source term estimation of the atmospheric release for the Fukushima Daiichi Nuclear Power Station accident by coupling simulations of an atmospheric dispersion model with an improved deposition scheme and oceanic dispersion model

Abstract: Abstract. Temporal variations in the amount of radionuclides released into the atmosphere during the Fukushima Daiichi Nuclear Power Station (FNPS1) accident and their atmospheric and marine dispersion are essential to evaluate the environmental impacts and resultant radiological doses to the public. In this paper, we estimate the detailed atmospheric releases during the accident using a reverse estimation method which calculates the release rates of radionuclides by comparing measurements of air concentration… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
202
4
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 277 publications
(239 citation statements)
references
References 103 publications
14
202
4
8
Order By: Relevance
“…The new scheme deals with dry and fog-water deposition, cloud condensation nuclei (CCN) activation, and subsequent wet scavenging due to mixed-phase cloud microphysics (in-cloud and below-cloud scavenging) for radioactive iodine gas (I2 and CH3I) and other particles (CsI, Cs, and Te) as shown in Fig. 2 [9]. …”
Section: Improvement Of Atdm Simulationmentioning
confidence: 99%
See 4 more Smart Citations
“…The new scheme deals with dry and fog-water deposition, cloud condensation nuclei (CCN) activation, and subsequent wet scavenging due to mixed-phase cloud microphysics (in-cloud and below-cloud scavenging) for radioactive iodine gas (I2 and CH3I) and other particles (CsI, Cs, and Te) as shown in Fig. 2 [9]. …”
Section: Improvement Of Atdm Simulationmentioning
confidence: 99%
“…For this purpose, the source term estimated by Katata et al [9] was the most appropriate one in the published source terms, and was used in this study. The temporal change in release rate of 131 I from 12 to 24 March 2011 estimated by Katata et al [9] is shown in Fig. 1.…”
Section: New Source Termmentioning
confidence: 99%
See 3 more Smart Citations